Variaciones en la cubierta forestal a largo plazo y su incidencia en los caudales de las cuencas hidrográficas del Cantón Valencia, provincia de los Ríos-Ecuador - Cobeña Gil, Kevin Joel (2022)
On the Ecuadorian coast, 95% of the forests have been felled due to agricultural activities, which has caused several of the flows to be affected by excess sediments due to poor agricultural practices, as well as the progressive use of chemicals. mics and fertilizers, which limits their use, however, the hydrographic basins are in a clear process of deterioration, with little power to control flooding in the rainy season and water scarcity during the dry season (1).